Etiological factors of Intussusception among children in a tertiary care hospital (Bangladesh Medical Journal Khulna, 2017)
Background: There are still dearth of knowlege of intussusception regarding its aetiology and predisposing factor among children.Objectives: We attempted to find out per operatively the etiological factors responsible for intussusceptions in children and their association with predisposing factors in our context. We also intended to know peroperatively the specific role of hypertrophid Peyer's patches of mesenteric lymph adenitis as lead points.Methodology: This prospective observational study was conducted in Khulna Medical College Hospital and other private hospitals in Khulna from November 2012 to April 2016. A total of 50 patients who underwent surgery for intussusception were included in the study. Seasonal influences, gastroenteritis and upper respiratory tract infections were evaluated as predisposing factors and presence of hypertrophied Peyer's patches and other lead points were evaluated as etiological factors. Peroperatively the causes were identified and their association with viral gastroenteritis and respiratory tract infection were intended to find out.Results: seventy two percent of the patients were below one year. A male preponderance was observed (70%). Thirty two percent were affected in the spring and 36% in the summer. Half (54%) of the patients had a history of gastroenteritis, while 40% had a history of respiratory tract infection. Per operative findings, show that three quarter (76%) had ileo colic, 18% had ileo ileo colic and only 6% had ileo ileal variety of intussusceptions. Forty two (89.3%) patients had hypertrophied Peyer's patches or Mesenteric lymphadenities.Conclusion: Hypertrophied Peyer's patches or Mesenteric lymphadenitis are the main etiological factor of intussusceptions in our children.Bang Med J (Khulna) 2016; 49 : 23-26